La Revelatio ecclesiae sancti Michaelis et son auteur - Pierre Bouet (Tabularia)
The Revelatio ecclesiae sancti Michaelis in monte Tumba was written at the beginning of the 9th century by a canon at Mont-Saint-Michel. It is composed of two parts : one (ch. IV to VII) is based on a traditional oral account of the founding of the sanctuary on Mont Tombe in Neustria, dedicated to Saint Michael by Aubert, a bishop of Avranches at the beginning of the 8th century; the other (ch. I to III and VIII) proposes a history of this mount and a theological conception of the role of Saint Michael the Archangel in the destiny of mankind. This document reveals the culture of a canon during the Carolingian Renaissance, who was stronglyinfluenced by constant readings of the Bible, the sermons of the Holy Fathers and the works of Gregory the Great. But he shows a certain critical insight in his appreciations and even a genuinely scientific precision in his detailed references to the geology, the geography and the historical evolution of the Mont. A linguistic analysis of the Latin text leads us to date its writing at the beginning of the 9th century and to link it with the considerable movement of canonic reform undertaken byemperor Louis the Pious from 816 onwards. This reform sought to organise the community life ofclerics and to impose the authority of the bishop on all the churches and sanctuaries in the diocese.